Aberrant proteins in the saliva of patients with oral squamous cell carcinoma - Jessie, K.; Jayapalan, J.J.; Ong, K.C.; Abdul Rahim, Z.H.; Zain, R.M.; Wong, Kum Thong; Hashim, Onn Haji (2013)
Confirmation of oral squamous cell cancer (OSCC) currently relies on histological analysis, which does not provide clear indication of cancer development from precancerous lesions. In the present study, whole saliva proteins of patients with OSCC (n = 12) and healthy subjects (n = 12) were separated by 2DE to identify potential candidate biomarkers that are much needed to improve detection of the cancer. The OSCC patients' 2DE saliva protein profiles appeared unique and different from those obtained from the healthy subjects. The patients' saliva 1-antitrypsin (AAT) and haptoglobin (HAP) chains were resolved into polypeptide spots with increased microheterogeneity, although these were not apparent in their sera. Their 2DE protein profiles also showed presence of hemopexin and -1B glycoprotein, which were not detected in the profiles of the control saliva. When subjected to densitometry analysis, significant altered levels of AAT, complement C3, transferrin, transthyretin, and chains of fibrinogen and HAP were detected. The increased levels of saliva AAT, HAP, complement C3, hemopexin, and transthyretin in the OSCC patients were validated by ELISA. The strong association of AAT and HAP with OSCC was further supported by immunohistochemical staining of cancer tissues. The differently expressed saliva proteins may be useful complementary biomarkers for the early detection and/or monitoring of OSCC, although this requires validation in clinically representative populations.